Molecular genetic analysis of the melanoma regulatory locus in Xiphophorus interspecies hybrids. Issue 8 (13th April 2017) - Lu, Yuan; Boswell, Mikki; Boswell, William; Kneitz, Susanne; Hausmann, Michael; Klotz, Barbara; Regneri, Janine; Savage, Markita; Amores, Angel; Postlethwait, John; Warren, Wesley; Schartl, Manfred; et al.
Abstract : Development of spontaneous melanoma in Xiphophorus interspecies backcross hybrid progeny, ( X. hellerii  × [ X. maculatus Jp 163 A ×  X. hellerii ]) is due to Mendelian segregation of a oncogene ( xmrk ) and a molecularly uncharacterized locus, called R(Diff), on LG5. R(Diff) is thought to suppresses the activity of xmrk in healthy X. maculatus Jp 163 A parental species that rarely develop melanoma. To better understand the molecular genetics of R(Diff), we utilized RNA‐Seq to study allele‐specific gene expression of spontaneous melanoma tumors and corresponding normal skin samples derived from 15 first generation backcross (BC1 ) hybrids and 13 fifth generation (BC5 ) hybrids. Allele‐specific expression was determined for all genes and assigned to parental allele inheritance for each backcross hybrid individual. Results showed that genes residing in a 5.81 Mbp region on LG5 were exclusively expressed from the X. hellerii alleles in tumor‐bearing BC1 hybrids. This observation indicates this region is consistently homozygous for X. hellerii alleles in tumor bearing animals, and therefore defines this region to be the R(Diff) locus. The R(Diff) locus harbors 164 gene models and includes the previously characterized R(Diff) candidate, cdkn2x . Twenty‐one genes in the R(Diff) region show differential expression in the tumor samples compared to normal skin tissue. These results further characterize the R(Diff) locus and suggest tumor suppression may require a multigenic region rather than a single gene variant. Differences in gene expression between tumor and normal skin tissue in this region may indicate interactions among several genes are required for backcross hybrid melanoma development.